2005
DOI: 10.1002/eqe.520
|View full text |Cite
|
Sign up to set email alerts
|

A practical method to transform frequency dependent impedance to time domain

Abstract: SUMMARYIn order to perform time history earthquake response analyses with consideration to both the dynamic soil-structure interaction and the non-linear behaviour of the structure, it is important to transform the soil impedance in the frequency domain to the impulse response in the time domain. In this paper, a new transform method with high practicality is proposed. First, the formulation of the proposed transform method is described. Next, the validity of the method is examined using an example problem who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 10 publications
0
23
0
Order By: Relevance
“…This figure shows that the results in each case almost correspond to each other as a whole, but some differences are discernible in lowfrequency ranges. This is because the differences in the time-delay components of the stiffness term for the impulse response have a great effect on the low-frequency range of the recovered impedance as shown in Reference [1]. Figure 6(b) expands the frequency range 0-4 Hz in Figure 6(a).…”
Section: Investigation Using Greatly Noncausal Impedance (In the Casementioning
confidence: 93%
See 1 more Smart Citation
“…This figure shows that the results in each case almost correspond to each other as a whole, but some differences are discernible in lowfrequency ranges. This is because the differences in the time-delay components of the stiffness term for the impulse response have a great effect on the low-frequency range of the recovered impedance as shown in Reference [1]. Figure 6(b) expands the frequency range 0-4 Hz in Figure 6(a).…”
Section: Investigation Using Greatly Noncausal Impedance (In the Casementioning
confidence: 93%
“…The author has studied the transform method of complex stiffness, which is strongly dependent on frequency, to the time domain [1] and proved the applicability of an approximate transform method of the noncausal impedance with large hysteretic damping [2].…”
Section: Introductionmentioning
confidence: 99%
“…Since this method was first developed in the 1980s, many transform methods in the time domain have been proposed and improved to overcome difficulties in various frequency dependencies in IFs (Wolf & Motosaka, 1989;Meek, 1990;Motosaka & Nagano, 1992;Hayashi & Katsukura, 1990). Nakamura (2006a;2006b;2008a;2008b) has developed various sophisticated transform methods that can deal with strong frequency dependency in IFs, non-causal impedance with large hysteretic damping, and soil nonlinearity.…”
Section: Introductionmentioning
confidence: 99%
“…During a severe earthquake the building and its surrounding soil exhibit nonlinear behaviour. It is thus desirable to be able to use this boundary in the time domain also.The author has previously studied how to transform TB to the time domain with high accuracy and ease in cases where the dynamic stiffness has a strong frequency dependency [3,4]. As part of these efforts, the author transformed TB of the 2-dimensional in-plane problem, which is equivalent to FLUSH, into the time domain, and showed that high-accuracy analysis is possible in the same manner as with the frequency domain.…”
mentioning
confidence: 99%